Correlation Between Body Weight and Linear Body Measurements in Adult Female Sahiwal Cattle - Sahu, Sambhuti Shankar; Choursia, Sahu, S.K.; Chaturvedani, A.K.; Prakash , Om (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The present investigation was conducted in the herd of pure bred Sahiwal cows maintained at Bull Mother Experimental Farm (BMEF) and Government Cattle Breeding Farm (CBF), Anjora, Durg (Chhattisgarh). A total of 193 adult female Sahiwal cattle over three years of age were used in the experiment. The animals were grouped into seven age groups, i.e. 3-4, 4-5, 5-6, 6-7,7-8,>8 years old, and overall. Body weight was found to be significantly (P
Keywords: Body weight; Body length; Height at withers; Heart girth; Sahiwal; Correlation